VD_FINDINFO Décision / 2014 / 848 vom 12. September 2014 - VD Tribunal cantonal (2014)
FICTION DE LA NOTIFICATION, DOMICILE CONNU, EMPRISONNEMENT | 354 CPP (CH), 88 al. 1 let. a CPP (CH), 88 al. 4 CPP (CH)